Follow-on offerings - Harper, Joel T.; Johnston, Jarrod; Madura, Jeff (Journal of Banking & Finance, 2004)
Previous research has determined that lockup provisions essentially defer sell-offs of shares by insiders, and therefore cause a pronounced decline in share price at the time the lockup provisions expire. However, some IPOs involve follow-on offerings that may allow some insiders to sell their shares before the lockup provision has expired. Our objective is to determine how follow-on offerings alter firm value above and beyond the typical lockup effects, and whether the effects are conditioned by firm-specific variables. We find that follow-on offerings elicit an average market response of 3.21% over a three-day period surrounding the filing date. In addition, the offerings experience adverse effects as of lockup expiration that are about 3.75% worse than other IPOs, after considering other factors. Based on the share price response at the time of the follow-on offering along with the share price response at the time of lockup expiration, the cumulative effects for IPOs complemented by follow-on offerings are about 6.96% weaker than for IPOs not complemented by follow-on offerings. Overall, follow-on offerings may benefit some insiders who can circumvent the lockup expiration date, at the expense of other investors.